5‐ and 10‐km mesh datasets of agricultural land use based on governmental statistics for 1970–2005. Issue 5 (9th July 2015) - Osawa, Takeshi; Kadoya, Taku; Kohyama, Kazunori
Abstract: Land use data serve as an essential part of large‐scale ecological research, such as landscape ecology and macroecological studies. For agricultural fields in Japan, existing time series statistical records can be used to convert map data according to a map of municipality units. In this data paper, we determined the areas of agricultural land use in Japan from 1970 to 2005, excluding small islands, at spatial resolutions of 5‐ and 10‐km mesh grid units, which are often referred to as the Five‐fold Mesh and Japanese Second‐order Mesh, respectively. The elements considered included total farmland, paddy fields, dry farmland, and orchards. In 2005, we included abandoned agricultural areas because the related data were available in the agricultural statistical records. The source data came from the Census for Agriculture, Forestry and Fisheries conducted by the Ministry of Agriculture, Forestry and Fisheries, Japan. The Datum was the Japanese Geodetic Datum 2000 (JGD2000). All of the datasets have open data licenses under the rules of the Creative Commons CC‐BY 4.0 International (https://creativecommons.org/licenses/by/4.0/legalcode ).